Monetary Policy and the Redistribution Channel - Auclert, Adrien (American Economic Review, 2019)
This paper evaluates the role of redistribution in the transmission mechanism of monetary policy to consumption. Three channels affect aggregate spending when winners and losers have different marginal propensities to consume: an earnings heterogeneity channel from unequal income gains, a Fisher channel from unexpected inflation, and an interest rate exposure channel from real interest rate changes. Sufficient statistics from Italian and US data suggest that all three channels are likely to amplify the effects of monetary policy. (JEL E21, E31, E43, E52)